An immune-modulating diet increases the regulatory T cells and reduces T helper 1 inflammatory response in Leishmaniosis affected dogs treated with standard therapy. Issue 1 (December 2015) - Cortese, Laura; Annunziatella, Mariangela; Palatucci, Anna; Lanzilli, Sarah; Rubino, Valentina; Di Cerbo, Alessandro; Centenaro, Sara; Guidetti, Gianandrea; Canello, Sergio; Terrazzano, Giuseppe
Abstract Background Clinical appearance and evolution of Canine Leishmaniosis (CL) are the consequence of complex interactions between the parasite and the genetic and immunological backgrounds. We investigated the effect of an immune-modulating diet in CL. Dogs were treated with anti-Leishmania pharmacological therapy combined with standard diet (SD Group) or with the immune-modulating diet (IMMD Group). CD3+ CD4+ Foxp3+ Regulatory T cells (Treg) and CD3+ CD4+ IFN-γ + T helper 1 (Th1) were analyzed by flow cytometry. Results All sick dogs showed low platelet number at diagnosis (T0). A platelet increase was observed after six months (T6) SD Group, with still remaining in the normal range at twelve months (T12). IMMD Group showed an increase in platelet number becoming similar to healthy dogs at T6 and T12. An increase of CD4/CD8 ratio was revealed in SD Group after three months (T3), while at T6 and at T12 the values resembled to T0. The increase in CD4/CD8 ratio at T3 was maintained at T6 and T12 in IMMD Group. A reduction in the percentage of Treg of all sick dogs was observed at T0. A recovery of Treg percentage was observed only at T3 in SD Group, while this effect disappeared at T6 and T12. In contrast, Treg percentage became similar to healthy animals in IMDD Group at T3, T6 and T12. Sick dogs showed an increase of Th1 cells at T0 as compared with healthy dogs. We observed the occurrence of a decrease of Th1 cells from T3 to T12 in SD Group, although a trend of increase was observed at T6 and T12. At variance, IMMD Group dogs showed a progressive decrease of Th1 cells, whose levels became similar to healthy controls at T6 and T12. Conclusion The immune-modulating diet appears to regulate the immune response in CL during the standard pharmacological treatment. The presence of nutraceuticals in the diet correlates with the decrease of Th1 cells and with the increase of Treg in sick dogs. Therefore, the administration of the specific dietary supplement improved the clinical response to the standard treatment in a model of CL.